Protection efficacy of mRNA-based SARS-CoV-2 variant vaccine in non-human primates - Dongrong Yi; Yongxin Zhang; Jing Wang; Qian Liu; Ling Ma; Quanjie Li; Saisai Guo; Ruifang Zheng; Xiaoyu Li; Xingong Li; Yijie Dong; Shuaiyao Lu; et al. (Acta Pharmaceutica Sinica B)
The rapid emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants that evade immunity elicited by vaccination has posed a global challenge to the control of the coronavirus disease 2019 (COVID-19) pandemic. Therefore, developing countermeasures that broadly protect against SARS-CoV-2 and related sarbecoviruses is essential. Herein, we have developed a lipid nanoparticle (LNP)-encapsulated mRNA (mRNA-LNP) encoding the full-length Spike (S) glycoprotein of SARS-CoV-2 (termed RG001), which confers complete protection in a non-human primate model. Intramuscular immunization of two doses of RG001 in Rhesus monkey elicited robust neutralizing antibodies and cellular response against SARS-CoV-2 variants, resulting in significantly protected SARS-CoV-2-infected animals from acute lung lesions and complete inhibition of viral replication in all animals immunized with low or high doses of RG001. More importantly, the third dose of RG001 vaccination elicited effective neutralizing antibodies against current epidemic XBB and JN.1 strains and similar cellular response against SARS-CoV-2 Omicron variants (BA.1, XBB.1.16, and JN.1) were observed in immunized mice. All these results together strongly support the great potential of RG001 in preventing the infection of SARS-CoV-2 variants of concern (VOCs).